Development of Pencak Silat Learning Media in the Form of Pocket Books for Junior High Schools - Raibowo, Septian; Syafrial; Arwin; Prabowo, Andika; Permadi, Andes (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2023)
This study aims to determine the feasibility of pocket books based on specific motion material for pencak silat self-defense activities in learning self-defense activities for class VII junior high schools and to determine the results of students' readability tests. The research method uses a type of development research or Research and Development (R&D). The population in thi study were students of class VII, totaling 109 students. Then the sampling technique using random sampling amounting to 30 people. Data collection techniques in research using observation, interviews, documentation, and questionnaires. Data analysis techniques in this study used data reduction, data presentation, conclusions and verification, feasibility analysis techniques and pocket book readability tests. The results of the research that has been carried out regarding the development of pencak silat learning media in the form of pocket books for junior high schools are pocket books that are "appropriate" for use as alternative teaching materials by PJOK teachers in schools, and pocket books that are very practical to use for students as a medium. This learning can be seen from the results of the readability test with the results of the percentage of the three aspects totaling 81.11 % categorized as Very Practical.